2021
DOI: 10.1001/jamaoto.2021.1548
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction Models for Suspected Pediatric Foreign Body Aspiration

Abstract: IMPORTANCEAlthough various clinical prediction models (CPMs) have been described for diagnosing pediatric foreign body aspiration (FBA), to our knowledge, there is still no consensus regarding indications for bronchoscopy, the criterion standard for identifying airway foreign bodies.OBJECTIVE To evaluate currently available CPMs for diagnosing FBA in children.DATA SOURCES Performed in Ovid MEDLINE, Ovid Embase, PubMed, Web of Science, and CINAHL database with citation searching of retrieved studies.STUDY SELEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…To his day, there are no valid clinical prediction models for FB aspiration. The decision relies on the astute clinical care tailored for each patient by an experienced clinician [49].…”
Section: Inhaled Foreign Bodiesmentioning
confidence: 99%
“…To his day, there are no valid clinical prediction models for FB aspiration. The decision relies on the astute clinical care tailored for each patient by an experienced clinician [49].…”
Section: Inhaled Foreign Bodiesmentioning
confidence: 99%
“…The clinical course and prognosis of FB inhalation depend on the size and location of the FB, as well as the time that the FB remains in the airway 12 . Therefore, prompt diagnosis and early treatment are crucial to prevent potentially fatal sequelae such as pneumonia, atelectasis, bronchiectasis and acute respiratory failure 13 . Plain chest X-ray is the main investigative tool in FB aspiration, but the de nite diagnosis and subsequent treatment, is provided only by rigid bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, systematic reviews of predictive models and methods of meta-analyses have been reported, which allow quantitative analysis of predictive models (Debray et al, 2017(Debray et al, , 2019Moons et al, 2014;Wolff et al, 2019). Subsequently, some scholars used these methods to conduct a systematic review and meta-analysis of prognostic prediction models for other diseases and obtained some meaningful results; some predictive models that can be widely used in clinical practice have been found (Bellou et al, 2019; J. J. W. Lee et al, 2021;Siriyotha et al, 2021). However, systematic reviews and meta-analyses of prognostic prediction models for hypoglycemia have not been found by authors.…”
Section: Introductionmentioning
confidence: 99%